2008
DOI: 10.1128/jvi.00782-08
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathogenicity of Classical Swine Fever Virus Correlates with Attenuation in the Natural Host

Abstract: For the important livestock pathogens classical swine fever virus (CSFV) and bovine viral diarrhea virus (BVDV), cytopathogenic (cp) and non-cp viruses are distinguished according to the induction of apoptosis in infected tissue culture cells. However, it is currently unknown whether cp CSFV differs from non-cp CSFV with regard to virulence in the acutely infected host. In this study, we generated helper virus-independent CSFV Alfort-Jiv, which encompasses sequences encoding domain Jiv-90 of cellular J-domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…To overcome this limitation, we included analyses of the genomic CP CSFV-JIV. The laboratory CP CSFV-JIV is a complex construct which was derived from the parental non-CP CSFV used in this study (10). CP CSFV-JIV was genetically engineered by the insertion of foreign genes from a CP BVDV isolate (BVDV CP8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome this limitation, we included analyses of the genomic CP CSFV-JIV. The laboratory CP CSFV-JIV is a complex construct which was derived from the parental non-CP CSFV used in this study (10). CP CSFV-JIV was genetically engineered by the insertion of foreign genes from a CP BVDV isolate (BVDV CP8).…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, CP CSFV isolates were rarely identified in the field and always represented helper virus-dependent defective interfering particles (DI) (19). A laboratory CP CSFV strain has been constructed (termed CP CSFV-JIV) according to the genomic organization of the cytopathic BVDV strain CP8 (10). The CP CSFV-JIV was highly attenuated in pigs compared to the parental non-CP CSFV (10).…”
Section: Classical Swine Fever Virus (Csfv) Belongs To the Genus Pestmentioning
confidence: 99%
See 1 more Smart Citation
“…The ncp biotype with its downregulated RNA replication efficiency seems to be a prerequisite for efficient control of the innate immune system by the viral virulence factors N pro and E rns as well as for evading induction of apoptosis (9,30). Also for CSFV, it has recently been demonstrated that an upregulation of NS2-3 cleavage correlates with induction of the interferon system and attenuation in the host (14). Therefore, control of NS2-3 cleavage plays a crucial role in the biology of pestiviruses in general.…”
Section: Discussionmentioning
confidence: 99%
“…All cells were maintained at 37°C and 5% CO 2 . ncp CSFV, cp CSFV-JIV, and a cp CSFV replicon were generated by transfection of a SP6 transcript of p447, p447-JIV (22), and p447-rep cDNA (18) clones as described previously (23). Nucleotide and amino acid numbers of CSFV throughout this study refer to the sequence of the parental ncp CSFV strain Alfort-Tuebingen (GenBank J04358.2).…”
Section: Lassical Swine Fever Virus (Csfv) Is the Causative Agent Omentioning
confidence: 99%